Response to chemotherapy in gastric adenocarcinoma with diffusion‐weighted MRI and 18F‐FDG‐PET/CT: Correlation of apparent diffusion coefficient and partial volume corrected standardized uptake value with histological tumor regression grade. Issue 5 (8th November 2013) - Giganti, Francesco; De Cobelli, Francesco; Canevari, Carla; Orsenigo, Elena; Gallivanone, Francesca; Esposito, Antonio; Castiglioni, Isabella; Ambrosi, Alessandro; Albarello, Luca; Mazza, Elena; Gianolli, Luigi; Staudacher, Carlo; et al.
<x xml:space="preserve">Abstract</x> Purpose To assess whether changes in diffusion‐weighted MRI (DW‐MRI) and 18F‐fluoro‐2‐deoxyglucose positron emission tomography/computed tomography (18F‐FDG PET/CT), correlate with treatment response to neoadjuvant therapy (NT), as expressed by tumor regression grade (TRG), from locally advanced gastric adenocarcinoma (GA). Materials and Methods Seventeen patients underwent both DW‐MRI and 18F‐FDG‐PET/CT scans before and after the end of NT. Apparent diffusion coefficient (ADC) and mean standardized uptake value (SUV) corrected for partial volume effect (PVC‐SUVBW‐mean) were evaluated and compared with histopathological TRG. Results Pre‐ and post‐NT and percentage changes for ADC and PVC‐SUVBW‐mean were assessed. Post‐NT ADC and ΔADC showed a significant inverse correlation with TRG (r = −0.71; P = 0.0011 and r = −0.78; P = 0.00020, respectively) and significant differences in their mean values were found between responders (TRG 1–2‐3) and nonresponders (TRG 4–5) (P = 0.0009; P = 0.000082, respectively). No correlations with TRG were found for pre‐NT ADC and for all PVC‐SUVBW‐mean values as well as between ΔADC and Δ PVC‐SUVBW‐mean. Conclusion DW‐MRI seems more accurate than 18F‐FDG‐PET/CT and ADC modifications may represent a reproducible tool to assess tumor response for GA. J. Magn. Reson. Imaging 2014;40:1147–1157. © 2013 Wiley Periodicals, Inc.